Validation of Perceived Stress Scale-10 Among Greek Middle Adolescents: Associations Between Stressful Life Events and Perceived Stress - Ntina Kourmousi; Kalliopi Kounenou; Christos Pezirkianidis; Antonios Kalamatianos; George P. Chrousos (Social Sciences, 2025)
Stress significantly impacts adolescents’ health. Therefore, its measurement is of critical importance. This study aims to assess the psychometric properties of a Greek adolescent version of PSS-10 among middle adolescents. This study’s questionnaire, which was completed by 169 adolescents aged 15–18, included a Greek linguistic, cultural, and age-appropriate version of the PSS-10 and the validated Greek ASQ version. Confirmatory factor and exploratory factor analyses were conducted. Convergent validity was tested through Pearson’s r intercorrelations among PSS-10 scales and ASQ and PSS-10 scales. Discriminant construct validity was determined by the association between PSS-10 scales and gender, grade, diploma grade, and following daily routines using Student’s t-tests or analysis of variance (ANOVA). Confirmatory factor analysis was not satisfactory. Exploratory factor analysis revealed two factors: perceived coping and perceived control, which explained 25.8% and 23.8% of the variance, respectively. Internal consistency reliability was satisfactory (Cronbach’s alpha > 0.70). Positive and significant correlations were found between ASQ and PSS-10 scores, indicating satisfactory convergent validity. Concerning discriminant validity, students who followed daily routines appeared to have less perceived stress. The Greek version of the 10-item Perceived Stress Scale (PSS-10) for adolescents is a valid instrument and can be used by professionals to rapidly screen perceived stress in adolescent populations.